Spectrum of adverse drug reactions and implicated drugs in a tertiary care centre: a prospective study - K., Kabilan; V., Sathyanarayanan; Rani, R. Jammuna (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adverse Drug Reaction(ADR) is the major limitation in providing health care to patients at a global level. It affects patient’s recovery and is an important cause of mortality and morbidity in both hospitalized and ambulatory patients. ADR can occur with any class of drugs. Early detection and evaluation of ADR is essential to reduce harm to the patients. Thus, the present study was aimed to estimate the number of ADR’s reported, analyze its spectrum and the drugs attributed to it. Methods: This was a prospective study conducted in a tertiary care teaching hospital for a period of 3 months from March 2016 to May 2016 in SRM Medical College and Hospital, Potheri. Adverse drug reactions were collected by spontaneous reporting by active and passive methods. The causality assessment of the reported ADR’s was done using Naranjo causality assessment scale. Results: A total of 38 ADR’s were reported during the study period with male predominance (58%). Most of the ADR’s (42%) were common in patients in the age group 19-39 years. More number of ADR’s were from Medicine (29%) followed by Surgery (16%) and OG (16%) departments. Most commonly affected organ systems were skin (45%) followed by GIT (24%). The drugs mostly accounted were antibiotics (55%) especially Cephalosporins (33%). Most of the reactions were type A (68%) rather than type B (32%) and thus predictable. According to Naranjo’s causality assessment, 63% of reactions were probable, 26% were possible and 11% were definite. No reactions were unlikely. Severity assessment by Modified Hartwig and Seigel scale revealed 45% ADRs to be moderate, 42% were mild and 13% were severe and life threatening. Conclusions: The study concluded that Adverse Drug Reactions are common and some of them resulted in increased healthcare cost due to need of some interventions and increased length of hospital stay. As majority of ADR is predictable (Type A), so preventable. The health system should promote the spontaneous reporting of Adverse Drug Reactions (May be done mandatory). The proper documentation and periodic reporting to regional pharmacovigilance centres to ensure drug safety.